Estudo do perfil químico e da atividade inseticida de Parahancornia amapa no controle de Atta sexdens - Franco, Lulliana (Universidade Federal de São Carlos, 2026)
Leaf-cutting ants of the genera Atta and Acromyrmex are important agricultural pests in Brazil, especially in Pinus and Eucalyptus plantations, due to the intense defoliation associated with the cultivation of the symbiotic fungus Leucoagaricus gongylophorus. Although chemical control is widely used, many conventional insecticides exhibit low biodegradability and high environmental impact, which has encouraged the search for alternative control strategies based on natural products. In this context, this study aimed to evaluate the insecticidal potential of Parahancornia amapa (Apocynaceae) in the control of Atta sexdens ants. Metabolites from leaves and bark were extracted using hexane and ethanol. The hexane extract from the leaves and the ethanolic extract from the bark showed significant insecticidal activity. Based on these results, the ethanolic bark extract, which exhibited 70% activity, was selected for bioguided fractionation, initially resulting in a more active methanolic fraction (≈90%). This fraction was subsequently subjected to liquid–liquid partitioning, yielding organic and aqueous subfractions. From the organic subfraction, three compounds previously unreported for the species were isolated and structurally characterized, belonging to the benzopyran class: one pterocarpan, one chroman, and one dimer. The isolated compounds showed moderate insecticidal activity; however, the highest activity was observed for the aqueous subfraction, which exhibited 68% mortality, suggesting a high content of condensed tannins. The comparison among the results obtained for the isolated compounds, the aqueous subfraction, and the original fraction indicated that the most pronounced insecticidal activity is associated with the combined action of the metabolites present in the sample, supporting the hypothesis of a synergistic effect. Additionally, the analysis of the chemical profile of the species by UHPLC-QTOF-MS/MS allowed the annotation of several secondary metabolites, including flavonoids, catechins, coumarins, iridoids, phenolic acids, pterocarpans, lignans, benzopyrans, and terpenes. The results obtained expand the knowledge of the chemical profile of P. amapa, which remains scarcely explored in the literature, as well as its biological potential, highlighting its relevance as a promising source for the sustainable control of leaf-cutting ants.
Study of the chemical profile and insecticidal activity of Parahancornia amapa for the control of Atta sexdens
Keywords: Formigas cortadeiras; Produtos naturais; Inseticida; Parahancornia amapa; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS; 12. Consumo e Produção Responsáveis